Relationship between right-to-left shunt and white matter lesions in patients with migraine: a single-center study - Liu, Zhihong; Jiang, Mingzhu; He, Jing; Lin, Yuchan; He, Lou; Li, Yan; Pan, Qi; Wu, Shan (Frontiers in Neurology, 2024)
The contents of this study were to first investigate the proportion of RLS in patients with different subtypes of migraine, to assess the relationship between RLS and different subtypes of migraine, and then to assess whether RLS w a s associated with a higher prevalence of white matter lesions. Our study showed that 41.9% of migraine patients had right-to-left shunt, and the proportion of RLS was 41.1% in migraine without aura and 55.8% in migraine with aura. The positive rate of RLS in migraine patients may not be related to the incidence of WML. Therefore, the research content of this study is consistent with the theme of your journal.